Resilient cyber-physical systems: a model predictive control scheme using perturbation analysis and sequential quadratic programming - Franze, Giuseppe; Tedesco, Francesco; Famularo, Domenico (2022 European Control Conference (ECC), 2022)
In this paper, a robust model predictive control strategy is developed for networked cyber-physical systems subject to false data injections. The aim of the proposed resilient architecture consists in quickly detecting data integrity anomalies and implementing adequate countermeasures. One of its relevant features is the capability to mitigate the use of periodic software rejuvenation procedures. This is achieved by on-line updating an initial sequence of admissible control moves via perturbations analysis and sequential quadratic arguments that are formally incorporated with detection and control phases.